Can drug-induced sleep endoscopy improve the success rates of tongue base surgery? - Jong-Gyun Ha; Youngwoo Lee; Jae Sung Nam; Jeong Jin Park; Joo-Heon Yoon; Chang-Hoon Kim; Hyung-Ju Cho (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The purpose of this study was to determine the therapeutic value of drug-induced sleep endoscopy (DISE) by comparing the outcomes of tongue base surgery based on Muller’s maneuver (MM) and those based on DISE in obstructive sleep apnea (OSA) patients. Methods Ninety-five patients who underwent the tongue base surgery in combination with palatal surgery for OSA at a tertiary referral hospital between March 2012 and March 2019 were enrolled in this retrospective comparative study. Forty-seven patients underwent MM for surgical decision and 48 patients underwent DISE in addition to MM for surgical decision. Surgical success was defined according to the Sher criteria (postoperative apnea-hypopnea index [AHI] < 20/h and ≥ 50% reduction in preoperative AHI), and AHI improvement (%) was defined as (preoperative AHI-postoperative AHI) × 100/preoperative AHI. For comparison between the MM and DISE groups, p-values were calculated using independent or paired t-tests for continuous variables and using chi-square test for categorical variables. Results By comparing the results of MM and DISE, consensus on the tongue base level showed insignificant concordance (kappa = 0.017, p = 0.865), whereas that on the oropharynx level showed fair agreement (kappa =0.241, p = 0.005). AHI, supine AHI, rapid eyeball movement (REM) AHI, non-REM AHI, and nadir oxygen saturation were all significantly improved after the tongue base surgery in both groups. The MM group showed a significant improvement in the Epworth sleepiness scale after the tongue base surgery (p = 0.014), whereas the DISE group did not (p = 0.165). However, there was no significant difference in the AHI improvement (MM group = 47.0 ± 32.0, DISE group = 48.3 ± 35.4, p = 0.852) and surgical success (MM group = 42.6%, DISE group = 45.8%, p = 0.748) between the groups. Tonsil grade (p < 0.05) and occlusion at the oropharynx lateral wall (p = 0.031) were significantly related to surgical success in the MM group. Conclusions In the judgment of the tongue base surgery, MM and DISE findings showed poor agreement. DISE might affect the surgical decision on the tongue base surgery in OSA patients; however, there was a lack of evidence regarding the superiority of DISE over MM with respect to the surgical outcomes.